(untitled) (Journal of Applied Oral Science, 2021)
Bio-C Pulpecto (Bio-CP) was recently developed as the first bioceramic root filling material for primary teeth. Objective: To evaluate the physicochemical properties of radiopacity, setting time, pH, cytocompatibility and potential of Bio-CP to induce mineralisation, compared with (1) Calen thickened with zinc oxide (Calen-ZO), and (2) zinc oxide and eugenol (ZOE). Methodology: Physicochemical properties were evaluated according to ISO 6876. Saos-2 (human osteoblast-like cell line) exposed to extracts of the materials were subjected to assays of methyl thiazolyl tetrazolium, neutral red, alkaline phosphatase (ALP) activity and mineralised nodule production. The results were analysed using one-way or two-way ANOVA and Tukey’s or Bonferroni’s post-tests (α=0.05). Results: All the materials showed radiopacity higher than 3 mm Al. Bio-CP had lower pH than Calen-ZO, but higher pH than ZOE. Calen-ZO and Bio-CP did not set. The setting time for ZOE was 110 min. The cytocompatibility order was Calen-ZO > Bio-CP > ZOE (1:2, 1:4 dilutions) and Calen-ZO > Bio-CP = ZOE (1:12, 1:24 dilutions) and Calen-ZO = Bio-CP > ZOE (1:32 dilution). Bio-CP induced greater ALP activity at 7 days, and greater mineralised nodule production, compared to Calen-ZO (p<0.05). Conclusions Bio-CP showed adequate physicochemical properties, cytocompatibility and potential to induce mineralisation.